LEGAL PROTECTION OF HOUSEHOLD CREDIT GUARANTEE AGAINST PENSION OF CIVIL SERVANTS IN THE CONCEPT OF WELFARE STATE - SITTI AISYAH (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Prosperous is the life goal of all people without knowing territory and nationality. All countries in the world are formed with the main objective to achieve prosperity for its inhabitants. Abraham H. Maslow as quoted by Soekidjo Notoatmodjo classifies human needs in the level of needs, hereinafter referred to as the hierarchy of needs. Human needs are categorized into five levels of hierarchy ranging from physiological needs, security guarantees, social needs, recognition and appreciation, and finally is the opportunity to develop themselves. Law No. 1 of 2011 concerning Housing and Settlement Areas explicitly emphasizes the need to increase community access to housing, including for Low Income Communities. Housing management is the responsibility of the state whose guidance is carried out by the central government and regional governments in that case housing and settlement development. Housing problems are one of the primary needs of the community. Where in the case of housing supply and development, it is inevitable that the public service sector is very vital in nature. Talking about housing means also talking about financing, increased development financing due to soaring land prices, construction costs, and the cost of infrastructure and environmental facilities affect the rising prices of home ownership. The government through the banking community provides a housing loan facility, commonly called a Home Ownership Credit. Home Ownership Credit is a credit facility provided by banks to individual customers who will buy or repair a house.